Dividend distribution prediction for small- and medium-sized enterprises in an emerging economy - Correa-Mejía, Diego Andrés (2025)
The possibility of predicting dividends is a determining factor for shareholders, investors, and management, since dividends are an important variable for firm value creation. This study aims to predict small and medium-sized enterprises’ (SMEs) dividend decisions in an emerging Latin American economy. Supported by a sample of 20,418 observations for the years 2016-2018, a boosting model is applied to establish the incidence of a set of financial indicators for dividend prediction. The findings reveal that none of the financial indicators alone can explain future dividend expectations, demonstrating the robustness of the boosting model applied, and confirming that companies that have distributed dividends in the past are consistent with their dividend policy. This work has methodological, academic, and practical contributions to the SME segment, to the context in which it is studied, and to other emerging economies. The empirical evidence provided opens the door to future research that will enhance and deepen the study of this financial decision.